Alternative sweeteners influence the biomass of oral biofilm - Razak, Fathilah Abdul; Baharuddin, B.A.; Akbar, E.F.M.; Norizan, A.H.; Ibrahim, N.F.; Yusoff, M. (Elsevier, 2017)
Objective Compact-structured oral biofilm accumulates acids that upon prolonged exposure to tooth surface, causes demineralisation of enamel. This study aimed to assess the effect of alternative sweeteners Equal Stevia®, Tropicana Slim®, Pal Sweet® and xylitol on the matrix-forming activity of plaque biofilm at both the early and established stages of formation.